The Impact of Work Environment, Work Motivation and Job Satisfaction on Dispatchers Performance at PT. PLN (Persero) UP2D Makassar - Muhammad Reza Mulyadi; Idayanti Nursyamsi; Andi Nur Bau Massepe (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
This paper aims to determine and analyze the influence of the work environment, work motivation, job satisfaction on the performance of Dispatchers at PT PLN (Persero) UP2D Makassar. The method used in this research is the Descriptive Analysis method using multiple regression. The population in this study were employees who worked at PT PLN (Persero) UP2D Makassar, namely Dispatchers, the sample in this study were 34 Dispatchers. Data collection uses observations, questionnaires, and documentation while testing the hypothesis used to use validity analysis techniques, reliability testing, classical assumption tests, partial tests, and simultaneous tests. The results of this study indicate that first, the work environment has a positive and significant effect on the performance of dispatchers. Second, work motivation has a positive and significant influence on dispatcher's performance. Third, job satisfaction has a positive and significant impact on dispatcher performance. Fourth, if simultaneously the influence of the work environment, work motivation, and job satisfaction on dispatcher performance together have a significant effect on performance. The most dominant variable in the model is work motivation, 34% explains the relationship to dispatcher employee performance variables.